Respuesta :

Answer:

Step-by-step explanation:

sec(-x) − sin(-x) tan(-x)

So the first step is often to write everything in terms of sine, cosine, or tangent.  So let's rewrite using sec x = 1 / cos x:

1/cos(-x) − sin(-x) tan(-x)

Now we need to deal with those -x angles.  For that, we use reflection identities:

sin(-x) = -sin x

cos(-x) = cos x

tan(-x) = -tan x

Therefore:

1/cos(x) − sin(x) tan(x)

Now let's rewrite tan(x) as sin(x) / cos(x):

1/cos(x) − sin²(x)/cos(x)

Factoring:

(1 − sin²(x)) / cos(x)

Using Pythagorean identity: sin²(x) + cos²(x) = 1.  So 1 − sin²(x) = cos²(x).

cos²(x) / cos(x)

And finally, we divide.

cos(x)